MITOS KECANTIKAN DALAM CERPEN "BOKKO-CHAN" KARYA HOSHI SHINICHI: KAJIAN KRITIK SASTRA FEMINIS - Visiaty, Arianty; Zuriyati, Zuriyati; Rohman, Saifur (Jurnal SORA - Pernik Studi Bahasa Asing, 2021)
This study aims to examine the myth of female beauty in the short story "Bokko-Chan" written by Hoshi Shinichi using a feminist literary criticism approach. This study examines data taken from the story and analyzed using Wolf's (2004) theory. Based on the results of the data analysis, two types of beauty myths were found, namely the beauty myth of outer beauty (young age) and inner beauty (beauty is coldness, a little naive and innocent, non-argumentative, and tough). This beauty myth addresses the ideology of the male author (Hoshi Shinichi), namely the ideology that supports the preservation of male domination or the patriarchal system. The preservation of this domination is done through the creation of the myth of the beauty of a woman so that in the end it will shackle the freedom of women to do what they want, reveal their thoughts, and express their feelings.